Strengthening Creative Entrepreneurship through Digital Marketing Education in Kwangsan Village, Sidoarjo - Choirul, Adi Basuki; Zakariya, Novie Andriani; Ulum, Syahrul; Roni, Mukhamad; Ilham, Moh. (Abdimas Indonesian Journal, 2026)
This community service activity aims to strengthen the creative entrepreneurship of the people of Kwangsan Village, Sidoarjo Regency through digital marketing education. This activity was motivated by the suboptimal use of digital media by village communities in marketing creative business products, even though the potential for local resources and financial capital was relatively adequate. The method used is a descriptive-participatory approach through Participatory Action Research (PAR) by involving the people of Kwangsan Village from the stage of needs assessment, planning, implementation, to evaluation. Education is focused on the use of social media, marketplaces, and digital content strategies as a means of marketing creative businesses. The results of the activity showed an increase in participants' knowledge and skills in digital marketing, which had an impact on increasing the readiness of the community in developing creative businesses based on local potential in Kwangsan Village. This activity contributes to strengthening the local entrepreneurial ecosystem and has the potential to become a model for sustainable village community empowerment in Sidoarjo Regency.